Capturing autonomy features for unmanned spacecraft with ARE, the autonomy requirements engineering approach. (June 2016) - Vassev, Emil; Hinchey, Mike
Abstract Along with the traditional requirements, requirements engineering for autonomous and self-adaptive systems needs to address requirements related to adaptation issues, in particular: (1) what adaptations are possible; (2) under what constrains; and (3) how those adaptations are realized. Note that adaptations arise when a system needs to cope with changes to ensure realization of the system's objectives. The autonomy requirements engineering approach converts adaptation issues into autonomy features where goal-oriented requirements engineering is used along with a model for generic autonomy requirements. The approach is intended to help engineers develop missions for unmanned exploration, often with limited or no human control.